Menelisik Jejak Keturunan Asli Palembang di Desa Padang Burnai - RM Mediansyah; Fitriah Fitriah (Tanjak: Sejarah dan Peradaban Islam, 2022)
This study discusses the history of the formation of Padang Burnai Village, Muara Pinang District, Empat Lawang Regency and how the socio-cultural living conditions of the natives of Palembang in Padang Burnai Village, Muara Pinang District, Empat Lawang Regency. This research is a qualitative research that uses a historical and sociological approach. The results of the research that has been done, the cultural conditions of the indigenous people of Palembang who are in the village of Padang Burnai, the indigenous people of Palembang still adhere to the original culture of Palembang, but there are some cultural acculturations. Among the latitude and palembang tribes, they influence each other, but both still adhere to their respective customs. Meanwhile, in terms of social life, at first the Palembang Tribe in Padang Burnai Village did not want to mix with the Lintang tribe because of the different languages ​​and many differences, but over time they were able to adapt and live side by side.